Study on the Potential of Utilizing the Agricultural Waste as Biosorbent for Heavy Metal Ions - Atan, M. F. (ENCON 2013, 2013)
The main aim of this study is to study the potential of using agricultural wastes like sugarcane bagasse and banana peels as biosorbent for the removal of heavy metal ions presence in the wastewater issued from the agriculture activities in Kota Samarahan, Sarawak. The biosorbent is analyzed by using Fourrier Transformer – Infra Red (FT-IR). Fourrier Transformer – Infra Red (FT-IR) is used to analyze all the elements presence in the bisorbent before it can be tested with sample that contains heavy metal ions. The study also investigates the effect of adding chemical modifier in increasing the sorption capacity of bisorbents. Two chemical modifiers which are tartaric acid and sodium dodecyl sulphate are tested. Consequently, the result shows that untreated and treated sugarcane bagasse with chemical modifier possesses more capacity of sorption than untreated and treated banana peels with chemical modifier because polysaccharides create more ligand when it reacts with heavy metal ions. Thus, the percentage of transmittance increases which show the percentage of adsorption of heavy metal ions by sugarcane bagasse.